A PERLINDUNGAN HUKUM TERHADAP ANAK PELAKU TERORISME DI INDONESIA DALAM PERSPEKTIF HAK ASASI MANUSIA - Lowing, Fenia S.G.; Emma V.T Senewe; Devy K.G Sondakh (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Children of terrorism cannot be considered as perpetrators of crimes, but victims of crime, victims of terrorism networks, victims of doctrine, exploitation of thoughts, propaganda from parents or adults around them so they must be protected specifically. Children like this should not be imprisoned, but must be educated, given counseling, rehabilitated and social assistance. Judging from the Law on the Juvenile Criminal Justice System, the imposition of death penalty and life imprisonment does not apply to perpetrators of criminal acts of terrorism who are under 18 years of age or who are still classified as children. The state is also obliged to provide special protection for children who commit acts of terrorism. As for the legal arrangements for child perpetrators of terrorism from the perspective of human rights in Indonesia, it is regulated in several national regulations. Keywords: child of terrorism, human rights